INSTITUTIONAL HIGHER EDUCATION AND DISTANCE LEARNING USING THE METHODOLOGY OF TECHNOLOGICAL IMPROVEMENT (World Economics and Finance Bulletin, 2023)
It is not wrong to say that the educational process remains complicated for humanity, which is suffering from various infectious viruses, earthquakes, and natural disasters. The issue of continuing the process online was accepted by many. Interruptions in proper means of communication for various reasons complicate this process. But the rapid improvement of distance education is the basis for further interpretation and application of this process.
Keywords: distance education; process; education; learner